2017
DOI: 10.1149/2.0391707jes
|View full text |Cite
|
Sign up to set email alerts
|

Review—Nonlinear Electrochemical Impedance Spectroscopy

Abstract: Nonlinear Electrochemical Impedance Spectroscopy (NLEIS) is a method of characterizing an electrochemical systems by applying a large amplitude sinusoidal perturbation signal. This article presents a comprehensive review of existing literature on NLEIS analysis development and applications. Two types of NLEIS reports available in the literature, viz. one in which only the fundamental impedance is studied and the other in which both the fundamental and higher harmonic responses are analyzed, are reviewed. Early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 64 publications
(208 reference statements)
1
67
0
Order By: Relevance
“…Another way of representing impedance plots is known as Bode plot in which the total impedance and also the phase angle, ϕ = tan −1 ( z ″/ z ′), vs frequency are plotted. The plots clearly demonstrated that the impedance is high in the low‐frequency side while it is low in the high‐frequency side and the current across the sample is mainly electronic/polaronic or Faradaic in nature . In Figure D, Bode plot for the sample Au 50 at a temperature of 600 K is presented.…”
Section: Resultsmentioning
confidence: 94%
“…Another way of representing impedance plots is known as Bode plot in which the total impedance and also the phase angle, ϕ = tan −1 ( z ″/ z ′), vs frequency are plotted. The plots clearly demonstrated that the impedance is high in the low‐frequency side while it is low in the high‐frequency side and the current across the sample is mainly electronic/polaronic or Faradaic in nature . In Figure D, Bode plot for the sample Au 50 at a temperature of 600 K is presented.…”
Section: Resultsmentioning
confidence: 94%
“…It is widely reported that when high‐amplitude voltage such as 500 mV (the voltage used in this study) is applied in EIS experiments, the system shows nonlinear behavior (Fasmin & Srinivasan, ; Lvovich, ). The EIS method applied in this study assumed a linear or pseudo‐linear response as did Harker and Maindonald () and Bauchot et al, (2000).…”
Section: Resultsmentioning
confidence: 99%
“…In cold-pressed olive and avocado oil extraction, the grinding step in the process ruptures the oil bearing cells to release the oil droplets into the fruit pulp (Petrakis, 2006;Woolf et al, 2009). It is widely reported that when high-amplitude voltage such as 500 mV (the voltage used in this study) is applied in EIS experiments, the system shows nonlinear behavior (Fasmin & Srinivasan, 2017;Lvovich, 2012). The EIS method applied in this study assumed a linear or pseudo-linear response as did Harker and Maindonald (1994) and Bauchot et al, (2000).…”
Section: Electrical Impedance Spectroscopymentioning
confidence: 99%
“…The pristine GO membrane (Fig. 4a) showed a distinct semicircle at high frequency that corresponded to the double layer capacitance of the Pt electrode-membrane interface and the charge transfer resistance (Rct) [31]. A distinct capacitive semicircle was also generated for the Al 3+ -modified GO membrane.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 92%